A simple and sensitive LC–MS/MS method for the determination of polyphyllin VII in rat plasma and its application to pharmacokinetic study. (9th March 2023) - Wang, Hao; Han, Han; Xu, Ying; Yang, Yishun
Abstract: Polyphyllin VII is an isoprene saponin extracted from Rhizoma paridis, and it can effectively suppress tumor initiation, growth, and metastasis. In this study, we aim to develop and validate an LC–MS/MS method for the quantification of polyphyllin VII in rat plasma using digoxin as the internal standard (IS). The plasma samples were precipitated with methanol, and the samples were separated on an ACQUITY BEH C18 column (2.1 × 50 mm, 1.7 μm). The mobile phase consisted of 0.1% formic acid solution and acetonitrile. The detection was performed in the multiple reactions monitoring mode, with the precursor‐to‐product transitions of m/z 1075.4 > 883.3 for polyphyllin VII and m/z 779.4 > 649.6 for the IS. The method showed excellent linearity over the concentration range of 0.5–1000 ng/ml, with a correlation coefficient of 0.9996 ( r  = 0.9996). The lower limit of quantification was 0.5 ng/ml. The inter‐ and intra‐day accuracy (relative error) ranged from −4.8 to 5.9%, and precision (relative standard deviation) was < 9.0%. The assay showed high extraction recovery, ranging from 90.6 to 95.6%. Polyphyllin VII was demonstrated to be stable under the storage conditions. The validated LC–MS/MS method was successfully applied to the pharmacokinetic study of polyphyllin VII in rats after oral, intraperitoneal, and intravenous administrations. The pharmacokinetic results indicated that polyphyllin VII showed low oral (5.86%) bioavailability and moderate (38.81%) intraperitoneal bioavailability.